Uterine septum dissection using minihysteroscopy with bipotrode 5-Fr bipolar electrode versus monopolar resectoscopy with a unipolar knife. Issue 3 (August 2015) - Youssef, Hamed M.; Elshamy, Maged; Shoker, Tarik; Goda, Hosam; Warda, Osama
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to compare the two procedures for uterine septum dissection: resectoscopy with monopolar knife versus small-diameter hysteroscopy fitted with a bipotrode 5 Fr reusable bipolar electrode. Design This was a randomized controlled study. Setting The study was conducted in a tertiary university fertility care unit. Main outcome measures Operative parameters (the use of general anesthesia, cervical dilatation, operative time, volume of fluid used for uterine distention, complications, and need for reseptoplasty) and reproductive outcome parameters (pregnancy, abortion, preterm delivery, and live birth rate) were evaluated. Participants and methods Eighty-four patients with evident incomplete uterine septum and a history of recurrent miscarriage or unexplained infertility, who underwent hysteroscopic metroplasty during the period from June 2005 to January 2010 were included in this study. Cases were randomly allocated into two groups: group A included 42 women who were subjected to the conventional hysteroscopic surgery using a resectoscope with a unipolar knife, and group B included 42 women who underwent resection with a 4-mm-diameter hysteroscope with bipotrode 5 Fr reusable bipolar electrode. The patients were followed up for 24 months. Results There was no statistically significant difference between the two groups as regards age, BMI, and duration of infertility. General anesthesia and cervical dilatation were used in all cases of group A, and in four cases of group B. Both operative time and volume of the fluid used for uterine distention were statistically significantly greater in group A than in group B (25.4±3.2 and 15.6±2.2 min, respectively, P<0.001; 1103±350.5 and 710.4±120.4 ml, respectively, P<0.001). There was no statistically significant difference between the two groups as regards operative complications, need for reseptoplasty, and reproductive outcome parameters. Conclusion Small-diameter hysteroscopy with bipotrode 5 Fr reusable bipolar electrode is as effective as resectoscopy with unipolar electrode as regards reproductive outcome. It is a safe outpatient procedure and is associated with significant reduction in the operative time, distending media, and postoperative stay. It could be used without anesthesia or cervical dilatation in the majority of cases.